(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2020)
Our project is basically a web based application that engages in security and the transmission of data through the network. As we know that security is now become a necessity in each and everyone’s life as there might be people who want to access your secret data for wrong purposes.So our system deals with the security issue by implementing steganography into our system. Steganography basically helps to hide secret messages and information embedded in a photograph or a video. This technique helps to prevent any third party user from accessing the secret message. iIn our project we are also using an encryption technique that is the “Tiny Encryption Algorithm”. Encryption also plays an important role in keeping the data from unauthorized people in real time environment such that the data is safe. After encryption, the file is implemented with steganography and is then transmitted through the network to the receiver. The receiver should have the same application to de-embed the file and then decrypt the same file to extract the original file. The goal of our project is to design a tool for providing security to the system during transmission of data through the network for the likes of military forces that have an essential need for communication for vehicle control, surveillance signal processing and is even more imperative in times of a war.